Clinical relevance of copeptin plasma levels as a biomarker of disease severity and mortality in critically ill patients. Issue 9 (5th July 2018) - Koch, Alexander; Yagmur, Eray; Hoss, Alexander; Buendgens, Lukas; Herbers, Ulf; Weiskirchen, Ralf; Koek, Ger H.; Trautwein, Christian; Tacke, Frank
Abstract : Background: Copeptin, also termed C‐terminal pre‐pro‐vasopressin or CTproAVP, mirrors endogenous vasopressin (anti‐diuretic hormone, ADH) activity and might thereby serve as a biomarker reflecting the biological stress level. We therefore hypothesized that copeptin plasma concentrations are associated with disease severity in critically ill patients and could predict mortality. Methods: We analyzed plasma copeptin levels in a prospective, single‐center, observational study comprising 218 critically ill patients at admission to the medical intensive care unit (ICU). Mortality was assessed during a 2‐year observational follow‐up period. Results: Copeptin plasma levels were significantly elevated in critically ill patients (n = 218) at ICU admission, as compared with 66 healthy controls. Neither sepsis as the cause of critical illness nor pre‐existing metabolic disorders (type 2 diabetes, obesity) were found to influence copeptin levels. On the contrary, plasma copeptin was closely associated with disease severity (eg APACHE‐II score) and correlated with biomarkers of inflammation, renal failure, metabolism, vascular tone, and tissue perfusion. Elevated copeptin levels at ICU admission predicted short‐term and long‐term mortality. Conclusions: Copeptin plasma concentrations are significantly elevated in critically ill patients, correlate with disease severity and predict ICU and long‐term outcome. Thus, copeptin could be a promising tool for prognostication and management of critically ill patients.